Fick principle and exercise pulmonary hemodynamic determinants of the six-minute walk distance in pulmonary hypertension. (September 2020) - Joseph, Phillip; Oliveira, Rudolf K.F.; Eslam, Roza B.; Agarwal, Manyoo; Waxman, Aaron B.; Systrom, David M.
The six-minute walk test is widely used to assess the severity and prognosis of pulmonary hypertension. However, the pathophysiology underlying a compromised six-minute walk distance is incompletely characterized. The purpose of this study is to evaluate the Fick principle and pulmonary hemodynamic determinants of the six-minute walk distance in patients with suspected pulmonary hypertension. Twenty-nine patients were retrospectively studied and underwent a right heart catheterization for the evaluation of suspected pulmonary hypertension. With the pulmonary artery catheter in place, patients were moved to a treadmill and completed a six-minute walk test. Fick cardiac output and indices of right heart afterload were calculated using continuous measurements of pulmonary vascular pressures, gas exchange, and mixed venous blood samples. Fifteen subjects who walked ≤ 348 m were compared to 14 subjects who walked > 348 m. Systemic oxygen delivery was impaired in six-minute walk distance ≤ 348 m compared to six-minute walk distance > 348 m (15.2 ± 6.2 vs. 23.2 ± 6.8 mL/kg/min, p < 0.01). Impaired oxygen delivery was due to a depressed cardiac index and decreased cardiac reserve demonstrated by the change in the stroke volume index (3.0 ± 14 vs. 17 ± 15 mL/min/m 2, p = 0.02). The six-minute walk distance positively correlated with oxygen delivery ( r = 0.501, p = 0.006) and inversely correlated with oxygen extraction ( r = 0.369, p = 0.049). A decreased six-minute walk distance was associated with an increased total pulmonary resistance ( r = 0.502, p = 0.006) and pulmonary vascular resistance ( r = 0.530, p = 0.003). In patients with suspected pulmonary hypertension, a decreased six-minute walk distance is due to compromised oxygen delivery, decreased cardiac reserve, and increased right ventricular afterload.